Implementing a home-based exercise program for patients with advanced, incurable diseases after discharge and their caregivers: lessons we have learned. (December 2015) - Siemens, Waldemar; Wehrle, Anja; Gaertner, Jan; Henke, Michael; Deibert, Peter; Becker, Gerhild
Abstract Background Palliative care (PC) patients experience loss of physical function which usually impedes mobility, autonomy and quality of life. We aimed at examining the feasibility of a home-based exercise program for patients with advanced, incurable diseases after discharge. Results This was a single-arm pilot study (WHO-ICTRP: DRKS00005048). The 12-week home-based program comprised strength, balance, flexibility and endurance components. Patients with a presumed life expectancy of 6–12 months were recruited during a 6-months period on a specialized PC and a radiation therapy ward. We chose the De Morton Mobility Index as primary outcome. Secondary outcomes were quality of life, 6-min walk test and others. A total of 145 patients were screened, 103 (98 %) out of 105 patients on the specialized PC ward could not be included, mostly because of a low performance status [n = 94; 90 %; Eastern Cooperative Oncology Group (ECOG) >2]. The only two eligible patients declined to participate. Eleven out of 40 patients (28 %) were eligible on the radiation therapy ward. However, only one patient (9 %) participated but dropped out 2 days later (upcoming surgery). Distance to the hospital (n = 3; 30 %) and considering additional tasks as "too much" (n = 3; 30 %) were most common reasons for non-participation. Conclusions Establishing a home-based exercise program for inpatients after discharge was not feasible mainly due to non-eligibility and lack of demand. For future trials, we suggest that choosing (1) outpatients with (2) an ECOG of ≤2 and (3) an estimated survival of ≥9 months could enhance participation in home-based exercise programs.